Medication Safety and Error Prevention in Emergency Care Settings (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Emergency medication mistakes injure patients and endanger their safety. Medication error reporting systems exist; however, ED medication mistake rates are still a global issue, especially in high-stress emergency settings. In a tertiary care emergency hospital in India, researchers looked at how often pharmaceutical delivery mistakes occur, what kinds of errors occur, what causes them, and how to avoid them. From October 2017 to December 2017, researchers at India's tertiary care hospital's emergency department conducted a cross-sectional observational study. The research included adult patients (≥ 18 years) who received drugs during ED staff working hours. Trained investigators observed medicine administration mistakes (omission, improper time, dose, unauthorized, route, inappropriate method, expired drug, and dosage form) and gathered prospective data. Medical and nursing charts included demographic, pharmaceutical, and clinical data. The research involved 311 randomly chosen patients. This SPSS 22 data analysis included descriptive statistics and ANOVA. There were 311 patients with 130 medication mistakes in 95, a prevalence rate of 30.5% (95% CI = 25.3 – 35.7%). There were 56.8% more medication errors in the red zone than in the yellow (35.8%), or green (7.4%). The most common pharmaceutical mistakes included analgesics (49.4%), cardiovascular drugs (35.7%), and anti-infectives (29.4%). The most frequent errors were improper time (46.9%), unapproved (25.4%), omitted (18.5%), and dosage (9.2%). No adverse patient events were caused by medication mistakes in this research. These statistics imply that severely unwell individuals make most ED drug mistakes. Administration mistakes, including drug timing and illegal medicine use, were the most prevalent ED errors. Standardized procedures, double-check systems, and staff education may reduce drug mistakes and improve emergency department patient safety.